Male reproductive system and spermatogenesis in the deep water crab Charyhdis smithii McLeay (Brachyura : Portunidae) - Balasubrahmanian, C P; Suseelan, C (Indian Journal of Fisheries, 2011)
Morphology of male reproductive tract and spermatogenesis of the potentially commercial deep water crab Charybdis smithii were studied in specimens obtained during the cruises of Fishery Oceanographic Research Vessel Sagar Sampada in the Indian seas. Male reproductive tract is composed of testis, vasa deferentia, ejaculatory duct and external penis. Vas deferens is classified into anterior vas deferens (AVD), middle vas deferens (MVD) and posterior vas deferens (PVD). The tubular testis comprises numerous acini or seminiferous lobules arranged around central seminiferous duct. The spermatogenesis involves the progressive reduction of cjftoplasm and only one developmental stage was found in one seminiferous lobule at a time. The simple ellopsid spermatosphores are lodged in the AVD. The epithelial cells in the proximal portion of AVD are cuboidal whereas distal portion of AVD has columnar epithelial cells.